Sunburn (fohia) Healing Effects of Noni: Is it a Mechanism Involving Its Inhibitory Effects on MMP, COX-2 and Cat-G Enzymes? - Afa K. Palu, Shixin Deng, Brett J. West, Jarakae Jensen, Rachel A. Sabin (Journal of Applied Pharmaceutical Science)
The aim of the present investigation was to evaluate whether extracts and preparations of noni fruit and leaf, a Polynesian traditional herbal medicine, inhibit MMP, COX-2 and Cat-G enzymes in vitro, as its mechanism of action for healing sun-burn known as fohia in Tonga. Noni leaf ethanolic extract (NLEE) inhibited MMP-1, -2, -3, and -9 enzymes concentration dependently with 0.517, 0.234, 0.184, and 0.302 mg/mL IC50, respectively. Noni fruit juice concentrates (NFJC) in 1 and 5 mg/mL concentrations, inhibited MMP-12 enzymes by 102, and 99%, respectively. NFJC and NLEE inhibited Cat-G enzymes concentration-dependently with 0.125,
Keywords: Photoprotection,MMP enzymes,cathepsin G,skin health,photoaging,noni.